Technologies and Architectural Education - Paredes Navarrete, Iván (Revista Universidad de Guayaquil, 2012)
The beginnings of the architecture go back to the era in which the man walked in search of shelter or how to protect of the inclemency and the animals, until the present time in which we observed the different spaces from the cities to be saturated of constructions made with high technology and diverse designs, which often causes discussions in the social surroundings. Discussion that it does not prevent that education learning of this discipline is permeable by the scientific advances and the appearance of new technologies, specifically computer science with the different components from creation and projection of the architectonic design. One of the greater impacts by hand occurs by the abandonment of the drawing and the made artistic graphical representation, practice that entails the observation and the cognition reflection, which assures the space thought that all aspiring to architect must acquire and who helps to form the artistic graphical language, indispensable to express the own visual speech of the architecture.